Pengembangan Media Pembelajaran Konkret Menggunakan Model RME Berbasis Etnomatimatikan untuk Meningkatkan Motivasi Belajar Siswa Kelas III SD Negeri 105375 Sukasari - Meirani; Ahmad Landongi; Aulia Putri; Fina Triana; Dhea Wafiq Mawaddah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop concrete learning media of the Realistic Mathematics Education (RME) model based on ethnomatematics by integrating local cultural elements, namely the traditional Batak Toba house, in order to improve students' understanding of the concept of flat shapes, especially isosceles triangles. The background of this study is the low motivation where students in mathematics learning still use conventional methods and the minimal use of relevant and interesting media in mathematics learning. The method used in the study is Research and Development (R&D) with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study involved grade III students of SD Negeri 105375 Sukasari. Data collection instruments were in the form of interviews, validation questionnaires, and documentation. The results showed that the concrete learning media developed were valid based on the results of the expert assessment of the material validator, namely 85%, teaching modules and media 80%, from the results stated practical and effective based on teacher responses 81%. This media helps students understand the concept of isosceles triangles through the Realistic Mathematics Education (RME) approach that links learning with local culture. Cultural integration in mathematics learning not only increases motivation, but also fosters a sense of love and appreciation for regional cultural heritage. Thus, concrete learning media based on traditional Batak Toba houses can be used as an innovative alternative in mathematics learning in elementary schools.